The nurse manager active in the prison system: Skills, knowledge and attitudes necessary to do the humanization of care (Research, Society and Development, 2021)
Introduction: We know that health care implemented in the prison system must be designed with the aim of providing the perceived shortages among Persons Deprived of Liberty (PPL). In view of this scenario, nurses must develop care as a social practice offering comprehensive care that must be performed in a humanized manner, with the use of qualified listening, thus providing quality care for the performance of care, respecting the ethical rights and duties of your profession. Objective: To identify the care practices performed by the nursing team for the PLP, knowing the skills, knowledge and attitudes necessary to make the humanization of nurses' care in a prison system. Methodology: This is a study with a qualitative approach, of the integrative review type, which had as a database the Virtual Health Library using the Health Sciences Descriptors (DeCS): health and nursing and prisons. Complete articles were selected, available in Portuguese, English and Spanish between 2016 and 2021. At the end of the application of the criteria, 11 articles emerged for the production of the content. Results: Various ways of providing humanized care to the PLP were observed, highlighting the valorization and recognition of health professionals and their articulation when promoting health and welcoming. Final Considerations: The research led to the conclusion that it is not enough to think about humanization focusing only on these people, it must also be emphasized that health professionals, as they are protagonists of the care process, need recognition and appreciation of work in these sectors.